NICU Discharge Feeding Bundle Improves Accuracy of Postdischarge Feeding Preparation and Potentially Prevents Readmission. (April 2019) - Vollrath, Kimberly; Rosenberg, Adam; Gabrielski, Lisbeth; Deacon, Jane; Marshall, Susan; Rihn, Andrew; Grover, Theresa
Abstract : Background: Hospitalized infants often need fortified human milk and formulas for growth in the neonatal intensive care unit and postdischarge. Parents must learn how to properly mix infant feedings. At the initial Children's Hospital Colorado follow-up visit, baseline data revealed a 50% rate of mixing inaccuracy of discharge feeding recipes and identified the readmission of 2 infants with life-threatening hypernatremia. A gap in discharge teaching was identified. A quality improvement project was implemented at 2 affiliated neonatal intensive care units. Purpose/Aim: The aim of this study was to improve parental comfort and efficacy in infant feeding preparation during hospitalization, reduce mixing inaccuracy postdischarge, and prevent readmission. The primary aim was to improve the accuracy rate at follow-up to 75% within 12 months and the sustain mixing accuracy rate at follow-up to above 95% for an additional 24 months. Methods/Interventions: A literature review was conducted; potential barriers were identified and strategies developed to recognize the relationships between the aim and the changes to be tested. Implementation of standardized teaching focused on the teach-back technique. Education included mixing demonstration and written instructions. Parents were expected to correctly mix the recipe 3 times before discharge. Results: Mixing accuracy at the initial clinic follow-up visit improved to 97%. No readmissions were reported from inaccurately prepared feedings. Implications for Practice: Collaborative quality improvement project with standardized teaching provided improved feeding safety and parental comfort with accuracy of discharge instructions. Primary care providers need to be aware of the importance of accurate formula or fortified human milk preparation and verify accuracy of the specific discharge recipes at the initial visit.